EKONOMI ISLAM DAN POLITIK HUKUM DI INDONESIA - Dudi Badruzaman (Aktualita : Jurnal Hukum, 2019)
ABSTRACTThis research will describe the history of modern Islamic economic and political relations with the law in an effort to formulate various Islamic economic laws. This article also describes the position of the Islamic economy in the Indonesian legal system so that a description of how Islamic economy can be implemented in the Indonesian economy will be obtained. This study aims to find a basis for the development of Islamic economic law in two periods, the New Order and the Reformation Era. So that Islamic economic instruments can be used as an important part of the mainstream of national economic policy, there needs to be a systematic effort to create a sharia economic political design. This design must include three main domains, namely the realm of regulation and the rule of law, the realm of institutional strengthening and expansion, and the realm of internalizing sharia economic values in the life of the state and society.Keyword: Islamic Economics, Politics of Law, and Governance ABSTAKPenelitian ini akan menguraikan sejarah hubungan ekonomi dan politik Islam modern dengan hukum dalam upaya merumuskan berbagai UU ekonomi Islam. Artikel ini juga menggambarkan posisi ekonomi Islam dalam sistem hukum Indonesia sehingga akan diperoleh deskripsi bagaimana implementasi ekonomi Islam dalam perekonomian Indonesia. Penelitian ini bertujuan untuk  mencari dasar bagi pengembangan hukum ekonomi Islam yang ada di dua periode, Orde Baru dan Era Reformasi. Agar instrumen-instrumen ekonomi syariah dapat dijadikan sebagai bagian penting dari mainstream kebijakan ekonomi nasional, maka perlu ada upaya sistematis dalam menciptakan desain politik ekonomi syariah. Desain ini harus mencakup tiga ranah utama, yaitu ranah regulasi dan aturan hukum, ranah penguatan dan ekspansi kelembagaan, serta ranah internalisasi nilai ekonomi syariah dalam kehidupan negara dan masyarakat. Kata kunci: Ekonomi Islam, Politik Hukum, dan Tata Hukum